Tapping the Markets : Opportunities for Domestic Investments in Water and Sanitation for the Poor - Sy, Jemima; Warner, Robert; Jamieson, Jane (Washington, DC: World Bank, 2014)
Developing country governments and the international development community are looking for ways to accelerate access to improved water and sanitation services beyond the Millennium Development Goal (MDG) targets. Countries do not have the capacity to meet the need for improved water supplies and sanitation services from public resources alone. These challenges present an opportunity for domestic enterprises in these growing markets. In fact, millions of poor and non-poor households rely on the private sector to meet their needs. The range of private sector services provided goes far beyond final service delivery. The domestic private sector is increasingly being viewed as a central part of the solution. Governments are increasingly interested in engaging with the private sector to increase access of the poor to services. Effective scale-up of access through the domestic private sector requires an understanding of the market potential, the state of entrepreneurs' operations, and factors that shape their business environment and investment decisions. This document examines private sector provision of piped water services and on-site sanitation services in rural areas and small towns, with case studies from several countries. The preferences and circumstances of poor households and the performance of enterprises that provide services directly to them are examined, as are commercial and investment climate factors that may affect enterprises' actual or perceived costs and risks.